The Impact of Hydrostatic Pressure on the Structural, Mechanical, Thermal, and Optoelectronic Characteristics of the RbV3Sb5 Kagome Compound: Ab initio Approach - Prianka Mondal; Md. Raihan Islam; Mst. Shamima Khanom; Farid Ahmed (ChemistryOpen)
Abstract We studied the RbV3Sb5 kagome compound's structural, mechanical, thermal, and optoelectronic properties. Mulliken and Hirshfeld population analysis found ionic and covalent connections in RbV3Sb5. The Born stability criterion shows that pure RbV3Sb5 is mechanically stable. The precise measurement of 3.96 indicates that our sample has higher machinability at 20 GPa. Low anticipated hardness of RbV3Sb5 suggests it can be used as a soft solid lubricant. Hardness ratings rise with pressure, however there are exceptions. Pressure causes large nonmonotonic changes in RbV3Sb5′s anisotropic characteristics. A comparable 20 GPa Zener anisotropic value, RbV3Sb5 has the highest. The structure's projected Debye temperature at 0 GPa is 284.39 K, indicating softness. Dispersion curves with negative frequencies suggest ground state structural dynamical instability. The structure has no negative‐energy phonon branches under 10 GPa stress. From band structure and density of state analysis, the structure behaves metallically under hydrostatic pressure. Also, the structure has maximal ultra‐violet conductivity and absorption. The absorption coefficient, conductivity, and loss function plots show uniform patterns at all pressures. As pressure rises, these graphs’ peaks blue shift.